Long-Term Follow-Up of Children Treated With Peginterferon and Ribavirin for Hepatitis C Virus Infection. Issue 1 (January 2017) - Haber, Barbara; Alonso, Estella; Pedreira, Alejandra; Rodriguez-Baez, Norberto; Ciocca, Mirta; Lacaille, Florence; Lang, Thomas; Gonzalez, Teresita; Goodman, Zachary; Yang, Zijiang; Jackson, Beth; Noviello, Stephanie; et al.
ABSTRACT: Objectives: The aim of the study was to describe the 5-year follow-up of children who received peginterferon and ribavirin in a global, open-label study. Methods: A 5-year follow-up study of 107 children and adolescents ages 3 to 17 years with chronic hepatitis C virus infection who received peginterferon and ribavirin for 24 or 48 weeks. No drugs were administered during follow-up. Results: Ninety-four patients were enrolled in the long-term follow-up portion of the study; the median duration of follow-up was 287 weeks (range, 73–339). Of 63 patients with sustained virologic response who were enrolled, 54 completed 5 years of follow-up; none had relapse in the 5-year follow-up period. Significant decreases in height z scores were observed during treatment. The effect of treatment on height z score was larger in patients treated for 48 weeks compared with those treated for 24 weeks (mean change from baseline to the end of treatment was −0.13 [ P  < 0.001] and −0.44 [ P  < 0.001] in the 24- and 48-week treatment groups, respectively). Among patients treated for 24 weeks, full recovery of height z scores to baseline was observed by 1 year of follow-up, whereas only partial recovery was observed during 5 years of follow-up in patients treated for 48 weeks (mean change from baseline to the final follow-up visit was −0.16 ( P  = NS) and −0.32 ( P  < 0.05) in the 24- and 48-week treatment groups, respectively). Similar patterns were observed for weight and body mass index z scores. Conclusions: Impairment of growth should be considered when assessing the risk-benefit profile of peginterferon/ribavirin therapy in children with hepatitis C virus infection. In deciding to treat children with chronic hepatitis C virus, considerations should include both deferring treatment in patients during optimal growth periods, and the possibility that interferon-free regimens may be available to children in the next 5 to 10 years. Abstract : Supplemental Digital Content is available in the text